Believe It or Not: A Literary Examination of the Banquet Scene in Joseph Ibn Zabara's The Book of Delight - Einat-Nov, Idit (Hebrew studies, 2019)
This paper proposes a new reading of the banquet scene in Joseph Ibn Zabara's The Book of Delight. This reading derives from the hypothesis that this art of storytelling is based on a poetic principle of uncertainty, and is therefore associated with the various forms of the ambiguous and the ambivalent and the qualities that are typically associated with them—a sense of confusion and disorientation and an inability to decide among contradictory insights or emotional responses. As I have argued elsewhere about other rhymed Hebrew stories, this approach is appropriate to the character of some of the most fascinating rhymed stories produced in medieval Hebrew literature. The paper will describe the poetic devices which are used in this scene for the purpose of creating the jolting effect of uncertainty.